Predictors of primary biliary patency loss following biliary-enteric reconstruction for iatrogenic bile duct injury: a retrospective cohort study from a tertiary referral center in Mexico - Escobar-González, Alejandra; Saavedra-Flores, Denisse R.; Álamo-Hernández, Michel V.; García-Félix, Itzel G. (International Surgery Journal, 2026)
Background: Iatrogenic bile duct injury is one of the most serious complications associated with cholecystectomy. Although its incidence is low, its clinical impact is substantial due to the associated morbidity and mortality, the need for complex reconstructive procedures, and the significant deterioration in patients’ quality of life. Methods: A retrospective cohort study was conducted. Patients who underwent biliary-enteric reconstruction for iatrogenic bile duct injury at a tertiary care center from 2018 to 2022. The primary outcome was loss of primary biliary patency during follow-up. Univariate analysis was performed to identify factors associated with this outcome, using statistical package for the social sciences (SPSS) 25. Results: A total of 73 patients were included. Primary biliary patency was achieved in 49 patients (67.1%), whereas 24 patients (32.9%) developed loss of primary biliary patency. Postoperative bile leak occurred in 22 patients (30.1%). On univariate analysis, postoperative bile leak was significantly associated with loss of primary biliary patency (OR 14.33; 95% CI 4.30–47.78; p<0.001). SG3 classification showed a trend toward association with loss of primary biliary patency, although statistical significance was not reached (OR 2.27; 95% CI 0.83–6.19; p=0.110). According to the Cho classification, 52 patients (71.2%) achieved favorable outcomes (grades A–B). Conclusions: Postoperative bile leak was significantly associated with loss of primary biliary patency following biliary-enteric reconstruction for iatrogenic bile duct injury. Early identification of this complication may allow closer surveillance strategies and timely detection of reconstructive failure.